Public Sector Transformation: Increased Efficiency and Innovation in the Digital Economy - Nurfadilah, Ayu; Haliah, Haliah (Darul Yasin Al Sys, 2024)
Public sector transformation is a must in responding to new challenges and taking advantage of opportunities that arise in the digital economy era. The aim of this study is to understand the role of efficiency and innovation in public sector transformation, as well as its impact on public performance and services. The research background covers the ever-evolving global dynamics, where advances in digital technology have fundamentally changed the economic landscape, encouraging the public sector to improve efficiency, responsiveness, and innovation in providing public services to society. The research methods used include literature studies, secondary data analysis, and direct surveys to stakeholders related to public sector transformation. The results show that a large number of government agencies have adopted digital technology as part of their transformation efforts. However, there are still significant challenges associated with the digital divide and lack of technological skills among bureaucracy. It also found that innovation and collaboration across sectors play an important role in designing holistic and effective solutions. The result of this study is that the transformation of the public sector towards increased efficiency and innovation has a significant impact on public performance and services. Digital technology adoption, technology skills development, innovation promotion, and cross-sector collaboration are key in achieving transformation goals. By combining these efforts, the public sector can create significant added value for society and position themselves for long-term success in the ever-changing era of the digital economy.